2011
DOI: 10.1016/j.jbiomech.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The use of magnetic resonance imaging to predict ACL graft structural properties

Abstract: Magnetic Resonance Imaging (MRI) could potentially be used to non-invasively predict the strength of an ACL graft after ACL reconstruction. We hypothesized that the volume and T2 relaxation parameters of the ACL graft measured with MRI will predict the graft structural properties and anteroposterior (AP) laxity of the reconstructed knee. Nine goats underwent ACL reconstruction using a patellar tendon autograft augmented with a collagen or collagen-platelet composite. After six weeks of healing, the animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 21 publications
5
90
0
1
Order By: Relevance
“…Our study agrees with previous work that demonstrated a significant correlation between CrCL graft volume and structural properties in animal models (Fleming et al, 2011; Biercevicz et al, 2013). The difference between the two MRI sequences in the degree of correlation with structural properties may relate to the slice thickness used for imaging (1 mm for 3D FSE Cube and 0.375 mm for VIPR-aTR).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study agrees with previous work that demonstrated a significant correlation between CrCL graft volume and structural properties in animal models (Fleming et al, 2011; Biercevicz et al, 2013). The difference between the two MRI sequences in the degree of correlation with structural properties may relate to the slice thickness used for imaging (1 mm for 3D FSE Cube and 0.375 mm for VIPR-aTR).…”
Section: Discussionsupporting
confidence: 93%
“…In a caprine model of CrCL reconstruction, correlation between CrCL graft volume and stiffness, failure load and anterior-posterior laxity was found after 6 weeks of healing (Fleming et al, 2011). In a porcine model, correlation of the CrCL graft volume with stiffness, yield load and maximum load was found after 15 and 52 weeks of healing (Biercevicz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the prior study did not find a significant correlation between structural properties and T2 values as a separate quantifiable variable. This could be explained by the single 6 week time point investigated with this study, which would have limited T2 values to one phase of graft healing.…”
Section: Discussionmentioning
confidence: 85%
“…20 It has recently been established that graft volume when measured in situ via MR imaging, also correlates with the graft structural properties, and that the correlation could be improved by normalizing the volume to the graft T2 relaxation time three months post-operatively in the caprine model. 5 While these findings are promising, the relationship between graft volume, grayscale value, and the graft structural properties throughout the healing process remains undocumented. Because bio-enhanced primary repair of the ACL is now proving to be efficacious in animal models, 19 it is also important to validate the relationships between graft volume, grayscale and the structural properties of repaired ligaments.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Research has correlated higher strength or biomechanical properties with lower graft or ligament SI 37,38 and larger graft or ligament volume. 37, 42,43 The same MR parameter that relates to graft biomechanical performance was also predictive of overall patient knee health and ACL reconstruction surgical outcomes. 39 Future methods of assessing graft maturity and healing through MRI may become an important clinical assessment tool to determine RTP; with greater understanding of when an ACLR has healed, it may elucidate when a graft may tolerate the forces required for athletic return.…”
Section: Mrimentioning
confidence: 99%